2012
DOI: 10.1007/s00128-012-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Cd, Pb, As, Hg, and Se in Hair of Residents Living in Villages Around Fenghuang Polymetallic Mine, Southwestern China

Abstract: Heavy metal levels in hair of residents living in villages around Fenghuang mine were investigated. Samples belonging to mine areas showed the highest values, with mean concentrations (mg kg(-1)) of 0.17 for Cd, 8.67 for Pb, 0.11 for As, 2.19 for Hg, and 0.64 for Se. Significant correlations (p < 0.01) were found between Cd-Pb, Cd-As, Pb-As, and Se-Hg. There is no significant difference in any of the elements among age groups. However, significant differences in Cd and Pb levels were found between genders. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
(19 reference statements)
2
18
0
Order By: Relevance
“…The level of hair Cd at IG is also greater than the median value reported by Chojnacka et al (2010) regarding the population of 20-year old people, living in an urban and industrial region of Poland. The median value of 0.2 mg g À 1 found at IG is quite similar to that (0.19 µg g À 1 ) found in the hair from people living in Altamira (Brazil), an area with environmental impact from activities of gold mining (Carvalho et al, 2009), to the mean value observed by Li et al (2012) in people living in villages around the Fenghuang polymetallic mine (China), and also comparable with that found in hair samples from children living near an abandoned cupric pyrite mine in Portugal (Pereira et al, 2004). Barbieri et al (2011) obtained geometric mean values of 0.07 and 0.03 mg g À 1 for school-aged children living close to a large mine in exploitation and near an important tin smelter of the Bolivian Altiplano.…”
Section: Qmeqas08h-02supporting
confidence: 68%
See 1 more Smart Citation
“…The level of hair Cd at IG is also greater than the median value reported by Chojnacka et al (2010) regarding the population of 20-year old people, living in an urban and industrial region of Poland. The median value of 0.2 mg g À 1 found at IG is quite similar to that (0.19 µg g À 1 ) found in the hair from people living in Altamira (Brazil), an area with environmental impact from activities of gold mining (Carvalho et al, 2009), to the mean value observed by Li et al (2012) in people living in villages around the Fenghuang polymetallic mine (China), and also comparable with that found in hair samples from children living near an abandoned cupric pyrite mine in Portugal (Pereira et al, 2004). Barbieri et al (2011) obtained geometric mean values of 0.07 and 0.03 mg g À 1 for school-aged children living close to a large mine in exploitation and near an important tin smelter of the Bolivian Altiplano.…”
Section: Qmeqas08h-02supporting
confidence: 68%
“…However, Pb levels at IG were mostly lower than the mean concentration of Pb observed in hair samples from in people living close to the active chinese mine of Fenghuang (Li et al, 2012).…”
Section: Qmeqas08h-02mentioning
confidence: 46%
“…The mine waste calcine piles have released mercury, which has significantly contaminated the local environment (Li et al., ; Qiu, Feng, Wang, Fu, & Shang, ). The Fenghuang area is located in Hunan Province (110°02'E, 28°01'N) and is well known for the presence of low‐temperature hydrothermal mercury sphalerite (Li, Zhang, Yang, & Li, ). The Xunyang area is located in Shanxi Province (109°25'E, 33°06'N) and remains an active mercury mine in China.…”
Section: Methodsmentioning
confidence: 99%
“…The Fenghuang area is located in Hunan Province (110°02'E, 28°01'N) and is well known for the presence of low-temperature hydrothermal mercury sphalerite (Li, Zhang, Yang, & Li, 2012). The Xunyang area is located in Shanxi Province (109°25'E, 33°06'N) and remains an active mercury mine in China.…”
Section: Site Description and Samplingmentioning
confidence: 99%
“…As far as exposure is concerned, the most important matter of current publications is drinking water pollution (Maity et al 2012;Deb et al 2012;Guha Mazumder et al 2012;Marchiset-Ferlay et al 2012;Chen et al 2012;Kumasaka et al 2013). Another contemporary issue coming into focus is environmental contamination from (former) mining activities (Coelho et al 2012;Li et al 2012;Chakraborti et al 2012) and from waste deposits (Moreno-Santini et al 2012).…”
mentioning
confidence: 99%